(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Bhagandara has been described by Acharya Sushruta as one among Ashtamaharoga (eight major diseases) which is difficult to cure. This disease has been described in Ayurvedic texts in great detail. The etiopathogenesis, symptoms, types, preventive measures and curative aspects have been mentioned in detail. Ayurveda recommends a multi-dimensional approach in the treatment of this callous disease. The para-surgical and surgical techniques mentioned by Acharya Sushruta have been found very effective in the management of Bhagandara and Ksharsutra treatment in this disease has emerged as an effective and safe remedy in its management which has been accepted globally. The introduction of modern surgical methods of Fistulotomy and Fistulectomy were initially considered a boon for the treatment of this disease but their long standing side effects such as incontinence and recurrence made these techniques unsuitable for the majority of the Fistula-in-ano patients and the majority of these patients are turning towards Ayurvedic Ksharsutra therapy for treating this notorious disease. The popularity and efficacy of Ksharsutra treatment can be assessed from this fact that modern Surgeons refer these patients to Ayurvedic Surgeons for their successful management.